PERANAN LEARNING SOCIETY PENDIDIKAN ISLAM DI PERUMAHAN PEGAWAI NEGERI SIPIL (PNS) KOTA METRO LAMPUNG - Nina Tisnawati (AT-TAJDID, 2017)
This research is titled the role learning society of Islamic  education in the housing of PNS Metro city, where in the life of modern society living in the house of the complex is famous for individual life and full of material competition, hence the need of community learning activity, the field of Islamic education is very much needed to build relationships with surrounding neighborhoods, civil servants of the city of Metro have enjoyed the role of community learning as one way to establish close community. The purpose of this study is to answer the question: What is the role learning society of Islamic l education role in PNS Metro city housing,? what are the activities of lerning society in PNS city housing Metro ..?. This research uses qualitative method with descriptive research, with inductive analysis, where the data is taken through informant around the research site and the document of activity that took place, this research took place in PNS city of Metro RW 15, RT, 45 & 46 of Yosomulyo sub district of Metro Metro City Center.This study discusses how the role learning societuof Islamic education in the PNS housing city of Metro, and it turns out that learning society plays an important role in the environment to improve the closeness and familiarity of the environment around to minimize the occurrence of individualistic and material competition. The Islamic educational education educational activities in the PNS Metro housing environment are as follows; the activities of the parents, the activities of the mothers' ta'lim assembly, the activities of the libraries, the activities of holiday seminars, the visiting activities from home and at the beginning with tausiyah, morning gymnastics, archery and cleaning activities a residential complex environment that aims to keep the gap and to establish neighborly neighbors.